2020
DOI: 10.1002/rcm.8947
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the metabolites of piperine via hepatocyte incubation and liquid chromatography combined with diode‐array detection and high‐resolution mass spectrometry

Abstract: Rationale Piperine, an alkaloid isolated from Piper nigrum L., has been demonstrated to have many pharmacological effects and several health benefits. The aim of this work was to study the metabolic profiles of piperine in mouse, rat, dog and human hepatocytes. Methods The biotransformation was carried out by incubating piperine with hepatocytes at 37°C. After incubation for 2 h, the samples were pretreated and analyzed using liquid chromatography combined with diode‐array detection and high‐resolution mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Examining PIP-incubated hepatocytes (of rats, dogs, mouse, and human), it was revealed that at least 20 primary and secondary metabolites are formed from PIP [ 28 ]. PIP is fragmented (the basic fragmentation is shown in Figure 2 ) by several steps of reaction to be converted into these metabolites, generally starting with the loss of the piperidine ring followed by the cleavage of the amide bond.…”
Section: Pip Metabolism and Effect On Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Examining PIP-incubated hepatocytes (of rats, dogs, mouse, and human), it was revealed that at least 20 primary and secondary metabolites are formed from PIP [ 28 ]. PIP is fragmented (the basic fragmentation is shown in Figure 2 ) by several steps of reaction to be converted into these metabolites, generally starting with the loss of the piperidine ring followed by the cleavage of the amide bond.…”
Section: Pip Metabolism and Effect On Neurodegenerationmentioning
confidence: 99%
“…Oral gavaging of PIP in rats yielded a number of metabolites by oxidation and/or cleavage of the piperidine ring, which were not found in feces, but only in the urine sample ( Figure 2 ). However, it is to be noted that PIP metabolites from rats and human are not the same; thereby, Li et al (2020) have used mouse, human, and rat hepatocyte to identify, characterize, and distinguish PIP metabolites of different species [ 28 ]. Using a thorough screening and analytical techniques containing LC/DAD-HRMS and MS/MS, they have identified 20 metabolites; of them, 5 are primarily from PIP and the remaining 15 are secondary to those 5 primary metabolites (C11, 12, 15, 16, and 18; shown in Figure 2 ).…”
Section: Pip Metabolism and Effect On Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat urine, all three metabolites could be detected [ 38 ]. In an in vitro study comparing the hepatic piperine metabolism in mouse, rat, dog and human hepatocytes, the predominant metabolic pathways included formation of a catechol derivate for all species; however, the metabolic pathways displayed species-specific differences in terms of types and quantities of metabolites [ 47 ].…”
Section: Kinetics and Metabolismmentioning
confidence: 99%
“…It has been well documented that the methylenedioxyphenyl moiety is ready to undergo cytochrome P450 enzyme–catalyzed metabolism, resulting in the formation of catechol derivative 10 . Such biotransformation may lead to reactive metabolites carbene and ortho ‐quinone intermediates that may bring some unwanted side effects 11–16 . Therefore, it is necessary to identify and profile the metabolites of OPA, especially the identification of reactive metabolites.…”
Section: Introductionmentioning
confidence: 99%